Influence of the use of technology through problem based learning and Inkuiri models are leading to scientific communication students class VII - Agung Setyawan; Nurfina Aznam; Paidi Paidi; Tyasmiarni Citrawati (OmniaScience, 2020)
Problem Based Learning (PBL) and guided inquiry learning model develops intellectual ability as part of mental process. The purpose of this research is to know the difference of scientific communication ability between students who learn to use PBL model and guided inquiry, and to know whether there is influence the use of technology through PBL model and guided inquiry model to student scientific communication. The experimental research was conducted in 2 schools (SMP & MTs) Grobogan District. Examples consisted of 10 classes with 6 PBL model learning models, 4 guided inquiry model and 1 control class. The sample size is 352 students. Instruments using student worksheets and student research reports. The analysis used a one way variance with a significance level of 5% supported by students' skill and classical completeness. The results show the PBL model by giving the video at the beginning of learning gives the biggest influence with the average 83.615. The conclusion of this research is the better model of PBL in terms of individual capability, guided inquiry model better in terms of classical mastery. Improving scientific communication skills more effectively using PBL by providing video at the beginning of learning, followed by guided inquiry model with scientific reasoning. scientific communication skills more effectively using PBL with early video-giving activities and guided inquiry models with scientific reasoning.